2019
DOI: 10.7570/jomes.2019.28.3.186
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between the Ratio of Visceral Fat Area to Subcutaneous Fat Area on Computed Tomography and Lipid Accumulation Product as Indexes of Cardiovascular Risk

Abstract: BackgroundVisceral obesity and cardiovascular disease are closely related. Research on relevant indexes of cardiovascular disease is particularly important. One of these indexes is lipid accumulation product (LAP). However, the relationship between LAP and the ratio of visceral fat area to subcutaneous fat area (V/S ratio) remains unclear.MethodsIndividuals who visited the university hospital health promotion center and underwent abdominal computed tomography (CT) were included in the study. We analyzed the V/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…In the present study, we found that the AFI significantly correlated with BMI, presence of comorbidities, and lipid profile parameters, confirming its role as a surrogate for obesity and excessive fat accumulation. In agreement with our findings, Kwon et al, demonstrated that higher AFI was independent predictor of higher BMI [23] . Another report showed similar findings [24] .…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we found that the AFI significantly correlated with BMI, presence of comorbidities, and lipid profile parameters, confirming its role as a surrogate for obesity and excessive fat accumulation. In agreement with our findings, Kwon et al, demonstrated that higher AFI was independent predictor of higher BMI [23] . Another report showed similar findings [24] .…”
Section: Discussionsupporting
confidence: 94%
“…First, LAP has been considered as an index for visceral fat and study has demonstrated that LAP is effective to predict visceral fat. 16 However, we did not assess visceral fat by computed tomography or magnetic resonance imaging, which are more accurate. Second, the influence of lifestyle factors on UA levels was not taken into consideration in the current study, which should be considered in the future researches.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that LAP is effective to predict visceral fat. [16][17][18] To date, a number of studies have been designed to focus on the association of LAP with hypertension, diabetes, non-alcoholic fatty liver disease, and cardiovascular disease. [19][20][21][22] But there is less evidence about the association between LAP and hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…The TG/HDL-C ratio is an unsophisticated tool to ascertain patients at increased risk for insulin resistance and CVD. It is used to determine subjects at risk and vary across ethnicity and race [7]. Ioachimescu [30] and Bruna [1] also detected correlations with LAP Index and fasting glucose, HDL-C and SBP in both general population and in patients at higher cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Its superiority is the simultaneous reflection of the anatomical and physiological changes of fat over accumulation in adults. According to international studies, LAP can demonstrate risk factors associated with CVD fairly well [7].…”
Section: Introductionmentioning
confidence: 99%